Windmill Numeracy Learning Media to Increase Learning Motivation for Class V Students at SD Negeri 4 Batuputih - Arnis saputri, Arnis saputri; Sari, Novita (MEKONGGA: Jurnal Pengabdian Masyarakat, 2025)
The main problem faced by students of SD Negeri 4 Batuputih, Batuputih District, Kolaka Utara Regency, is the low motivation and understanding of numeracy concepts in Mathematics learning. Students tend to be passive and less enthusiastic, as they perceive Mathematics as difficult and uninteresting. To address this issue, this community service activity was carried out through the Kampus Mengajar Batch 8 program by introducing the Numeracy Windmill learning media as an interactive and game-based educational tool. The method consisted of planning, implementation, mentoring, and evaluation stages conducted collaboratively with teachers and students. The results showed a significant increase in students’ learning motivation by 77% and numeracy comprehension by 71%. This media proved effective in creating a fun learning environment, enhancing student engagement, and helping teachers deliver mathematical concepts in a simpler and more engaging way.